Iron regulatory proteins: players or pawns in ferroptosis and cancer? - Cardona, Cameron J.; Montgomery, McKale R. (Frontiers in Molecular Biosciences, 2023)
Cells require iron for essential functions like energy production and signaling. However, iron can also engage in free radical formation and promote cell proliferation thereby contributing to both tumor initiation and growth. Thus, the amount of iron within the body and in individual cells is tightly regulated. At the cellular level, iron homeostasis is maintained post-transcriptionally by Iron Regulatory Proteins (IRPs). Ferroptosis is an iron-dependent form of programmed cell death with vast chemotherapeutic potential, yet while IRP-dependent targets have established roles in ferroptosis, our understanding of the contributions of IRPs themselves is still in its infancy. In this review, we present the growing circumstantial evidence suggesting that IRPs play critical roles in the adaptive response to ferroptosis and ferroptotic cell death and describe how this knowledge can be leveraged to target neoplastic iron dysregulation more effectively.Author Contributions CC and MM contributed equally to reviewing and interpreting the relevant literature, drafting, and editing the manuscript.